Analisis Tingkat Kepuasan Pengguna pada Aplikasi Media Pembayaran OVO : (Studi Kasus: Kota Prabumulih) - Yuntari PURBASARI; Nurmayanti Nurmayanti (Repository STMIK Prabumulih, 2021)
Prabumulih city is located in the province of South Sumatra, has a population of 200.087 people aged seventeen years and over. Based on what can be sourced from the Department of Population and Civil Registration, a research sample of 80 people can be determined, to test the usability of the OVO application from the user side. The results showed that the five variables used consisted of learnability, efficiency, memorability, error, and satisfaction, namely: based on calculations using intervals from the Likert scale, for OVO applications only had two variables whose final value was greater, namely the learnability and satisfaction variables. It can be concluded from the learnability variable that it is easier for users to learn the OVO application, which means that users are easier to understand and learn OVO both from the existing menus, easy to make transactions, while on the satisfaction variable it can be concluded that on the satisfaction variable, users like the look and feel. services on the OVO application and the fast response carried out by the OVO application.